ISLAMISASI ILMU ISMAIL RAJI AL-FARUQI - Zuhdiyah Zuhdiyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2016)
al-Faruqi was the figure of a productive, all his writings are basically bright ideas and theories to fight for science integration project, which is packaged in a large frame Islamization of science. The idea of Islamization of science are in fact emerged as a response to the dichotomy between theology and science are incorporated Western secular modern society and culture of the Islamic world. Progress of modern science has brought a stunning effect, but on the other hand is also a negative impact, because the science of modern (Western) values dried or separated from religious values. For the Islamization of knowledge is a necessity that can not be bargained again by Muslim scientists.